Functional Multiplicity of an Insect Cytokine Family Assists Defense Against Environmental Stress - Shears, Stephen B.; Hayakawa, Yoichi (Frontiers in Physiology, 2019)
Growth-blocking peptide (GBP) constitutes a cytokine family identified in many insect species spanning six orders. Approximately 20-30 amino acid GBPs are predominantly synthesized in the fat body as relatively short inactive precursors (proGBPs), and then secreted into the hemolymph. When insects are exposed to stressors, a specific serine protease cleaves proGBPs near their carboxyl termini to release the active GBPs. The latter in turn stimulates expression of another insect cytokine, stress-responsive peptide (SRP), in the armyworm. It has been also demonstrated that, in Drosophila, the biologically-responsive, cell-surface receptor for GBP is the Methuselah-like 10 (Mthl10) G protein-coupled receptor. Active GBPs play a crucial role in regulating a variety of physiological and developmental aspects such as embryonic morphogenesis, larval growth rates, feeding activities, and immune responses. Therefore, the fine-tuning of these functions of active GBPs must be crucial for the survival of insects. Here we review the functional roles and regulatory mechanisms of GBP signaling.